2015
DOI: 10.1097/ogx.0000000000000146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enhanced Information, Values Clarification, and Removal of Financial Barriers on Use of Prenatal Genetic Testing

Abstract: Importance-Prenatal genetic testing guidelines recommend providing patients with detailed information to allow informed, preference-based screening and diagnostic testing decisions. The effect of implementing these guidelines is not well understood.Objective-Toanalyze the effect of a decision support guide and elimination of financial barriers to testing on use of prenatal genetic testing and decision-making among women of varying literacy and numeracy levels. Design-Randomized trial conducted from 2010-2013.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Previous studies have reported on the application of booklets with worksheets, 22,23 information films, 24,25 and interactive computer programmes. [26][27][28] Although results from these studies cannot easily be compared because of heterogeneity in settings, interventions and outcome measures, most have general findings that correspond with the results of the present study. Nearly all found the application of a decision aid to increase pregnant women's decision-relevant knowledge [22][23][24][25][26][27] and informed decision-making.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Previous studies have reported on the application of booklets with worksheets, 22,23 information films, 24,25 and interactive computer programmes. [26][27][28] Although results from these studies cannot easily be compared because of heterogeneity in settings, interventions and outcome measures, most have general findings that correspond with the results of the present study. Nearly all found the application of a decision aid to increase pregnant women's decision-relevant knowledge [22][23][24][25][26][27] and informed decision-making.…”
Section: Discussionsupporting
confidence: 76%
“…[26][27][28] Although results from these studies cannot easily be compared because of heterogeneity in settings, interventions and outcome measures, most have general findings that correspond with the results of the present study. Nearly all found the application of a decision aid to increase pregnant women's decision-relevant knowledge [22][23][24][25][26][27] and informed decision-making. 23,25 In this trial, high baseline levels of informed decision-making in the control group notwithstanding the application of the web-based multimedia decision aid resulted in an increase in informed decision-making that was slightly higher than the effect found in previous evaluations.…”
Section: Discussionsupporting
confidence: 76%
“…Because of the small amount of time in early prenatal visits devoted to discussion of genetic tests and the increasing number and complexity of testing options available, there are concerns that women are making decisions after receiving only minimal information and with poor understanding . In response, various modalities to evaluate risk, provide education, and support decision‐making for prenatal testing have been developed and evaluated, and Minkoff and Berkowitz have suggested all women meet with a genetic counselor early in pregnancy to review personal genetic risks and testing options.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at practices of genetic counselors, one finds that they usually focus on information derived from a risk analysis, leaving the task of weighing various possible outcomes to the “patient.” In a major study in California, women were encouraged to consider all their options—including the option of foregoing testing altogether—in the light of their own values. The findings of their study show that they were less likely to opt for invasive testing (Kuppermann et al, ). The wider approach to relevant information for informed decision‐making not only improved patient knowledge of the risks involved, but also showed that weighing these risks in view of their own values created a moral space to decide not to participate that earlier studies suggested women did not experience.…”
Section: The Task Of Fact‐finding Ii: Prenatal Screening and Testingmentioning
confidence: 95%